ST-33 Seismic behavior of reinforced concrete slab column connection with various corroded reinforcing bar - Muhammad Bin Mohamed Yusoof Basheer (Nanyang Technological University, 2023)
The use of reinforced concrete is widely considered to be the most common construction material in the world. While concrete has very high compressive strength, steel reinforcement bars compensate for the lack of tensile strength, making reinforced concrete an extremely versatile material. Corrosion has been shown to have a long-term detrimental effect on reinforced concrete and it is described thoroughly with examples of how corrosion influences the integrity and ultimate strength capacities of connections and concrete. Slab-column connections are often used to transfer loads from the slab to the column, which is seldom used for seismic forces, but often used for gravity loads. The slab-column connection is vulnerable to punching failure when there is a localised force acting on the connection. This report focuses on project experiments on the seismic behaviour of Grade 40 reinforced concrete slab column connections with different corroded and non-corroded slabs. The slabs were cast and corroded to specifications later mentioned in the report. However, only two sets of experiments in this report were done as the rest were delayed due to equipment failures and time constraints in the PE laboratory. Grade 40 concrete slabs were cast with and without various reinforcements to compare the differences in how the corroded reinforcement affects the concrete. The slab dimensions are 2100 mm × 1175 mm × 150 mm, and the supporting column dimensions are 250 mm × 250 mm × 300 mm. The aim of conducting tests is to examine the impact of corrosion on the seismic behaviour of slab-column connections made of reinforced concrete.